Тhe Possibilities of the Post-modern Methodology in Contemporary Practice of Psychological Help - Mykolaychuk, M. (Psychological Prospects Journal, 2013)
The article presents a theoretical analysis of the impact of postmodern philosophy on the current state of psychological science and practice. The modern theoretical trends and models of psychological counseling are considered. It covers the new features of postmodernism impact on contemporary psychological practice.